SEMEN QUALITY RESPONSE OF GROWING YANKASA RAMS FED DIET CONTAINING HOG PLUM (Spondias mombin) LEAF MEAL - Bishir, B.B.; Zahraddeen, D.; Iyeghe-Erakpotobor, G. T.; Abdulrashid, M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study investigates the effects of dietary inclusion of hog plum (Spondias mombin) leaf meal, on Semen quality, of growing Yankasa rams. The research was conducted at the Small Ruminant Research Programme, NAPRI, Ahmadu Bello University, Zaria. A total of 16 healthy Yankasa rams, aged 7–8 months and weighing between 16 and 24 kg, were randomly allotted to four dietary treatments with four rams per treatment in a completely randomized design (CRD). The diets formulated at graded inclusion levels of hog plum leaf meal (10%, 20%, and 30%) a control concentrate (0%) diets without hog plum leaves. The feeding trial lasted for three months. All data collected were subjected to analysis of variance (ANOVA) using general linear model SAS while significant differences among treatment means were compared using Duncan multiple range test. Semen samples were collected using electro-ejaculation. Parameters included semen volume, color, sperm concentration, motility, and pH. Results indicated no significant differences (P>0.05) among treatment groups for semen volume, motility, concentration or pH. Specifically, semen volume ranged from 0.23 to 0.55 ml, sperm motility remained within 57.50% to 76.25%, and sperm concentration was consistent across treatments, all within the normal reference values. Additionally, semen pH were unaffected, and mortality rates showed (P>0.05) no significant variation. Semen quality parameters remained within reference ranges, suggesting that inclusion of hog plum leaf meal up to 30% does not adversely affect semen characteristics in Yankasa ram. Farmers and animal nutritionists can consider incorporating hog plum leaf meal into ram diets at levels up to 30% without adversely affecting semen quality, which can aid in cost-effective feeding strategies, thereby contributing to more strategic utilization of available feed resources in Northern Guinea Savannah Zone of Nigeria.